Índice verde urbano para la elaboración de un plan de manejo de áreas verdes en la Parroquia Ángel Pedro Giler, Tosagua - Manabí - Moreira Almeida, Génesis Daniela (2023)
The purpose of this investigation was to determine the urban green index (IVU) in "Angel Pedro Giler" parish for the elaboration of a management plan for green areas. Therefore, three phases were proposed, starting with obtaining the index, where the number of existing green areas in the parish were identified and quantified, with a total of 19, classified into parks, gardens, street edges with palm groves and flower beds. With the total sum of the surface of the green areas and the total number of inhabitants in the urban area, the urban green index was calculated, which reflected 2.62m2/inhabitant; ultimately, the diversity of species in the identified areas was assessed by applying the Simpson, Shannon - Wiener and Pielou indices, presenting a total of 59 introduced and 9 native species with medium diversity and low dominance. In the second phase, a socioeconomic and environmental analysis was carried out through a survey of the inhabitants of the parish and the calculation of the importance index, which was based on social, economic and environmental variables, through this, it was revealed that the areas obtained a low rating, evidencing that there is no management in the green areas. At the end of the last phase, a management plan for green areas was prepared, which was shared with the highest authority of the parish GAD.